Association between event-related disclosure and posttraumatic growth: Targeting Japanese people, measuring attitudes toward disclosure, and examining event-related rumination as a mediating variable - Yuto Kimura; Takahiro Kozuka (PLoS ONE, 2026)
This study examined the association between event-related disclosure and posttraumatic growth (PTG). Specifically, it targeted the Japanese adult, assessed attitudes toward event-related disclosure, and examined event-related rumination as a mediating variable. A cross-sectional online survey was conducted among Japanese adults aged 20–59. Participants completed measures of demographic characteristics, stressful life events attributes, attitudes toward disclosure, event-related rumination, and PTG. Analysis of data from 480 individuals revealed that neither willingness to disclose nor resistance to disclose was directly associated with PTG. However, both willingness to disclose and resistance to disclose were positively associated with PTG through deliberate rumination and negatively associated with PTG through intrusive rumination. The effect sizes for willingness to disclose were approximately three times greater than those for resistance to disclose. These findings suggest that event-related disclosure may enhance PTG by promoting deliberate meaning-making processes, while also potentially hindering it by reinforcing involuntary negative thinking. Furthermore, these effects may be stronger when individuals are more proactive and disclose more frequently. These results have important implications for interventions aimed at enhancing PTG through event-related disclosure.